Greenfield vs Acquisitions: determinants of choice in emerging economies - Kamal, Shawkat (BRAC University, 2010)
This paper aims at finding determinants of entry mode choices for MNCs that enter emerging economy nations as wholly owned subsidiaries. Existing literature suggests that this area of international business literature is relatively understudied and reasons for conducting more research exist. In this paper, i test three hypotheses using a logistic regression model. More specifically, this paper looks at the role of contributed assets and organizational learning and experience in determining the choice between greenfield entry and acquisitions. The results suggest that host country experience and past entry experience has an impact on the current entry mode choice.